Four new species of the jumping spider genus Portia (Araneae, Salticidae) from China - Xin Xu (Pensoft Publishers, 2021)
We diagnose and describe four new species of Portia Karsch, 1878 and describe for the first time the male of P. zhaoi Peng, Li & Chen, 2003 from China based on morphological characters. The females of Portia bawang sp. nov. have the narrowest epigyne orifice. The males of Portia erlangping sp. nov. have the shortest embolus among all the species. The females of Portia fajing sp. nov. can be distinguished from other species by the anterior orifice margin, which is nearly parallel to the posterior orifice margin. The males of Portia xishan sp. nov. can be identified by the tegular furrow which extends to form a membrane and by the tegular apophysis which is obscured; the females of Portia xishan sp. nov. can be diagnosed by the slit-like epigynal orifice. The males of P. zhaoi have the longest embolus among all the species, and females can be diagnosed by the circular epigyne orifice and the longest copulatory ducts. To facilitate future identification, we also provide the GenBank accession codes of the DNA barcode gene, Cytochrome c oxidase subunit I (COI), for all the type specimens.